Socio-demographics influence on hospitality employee job insecurity, work engagement, financial concern, quality of life and mental health - Che Ahmat, Nur Hidayah; Rahamat, Syafiqah; Arendt, Susan Wohlsdorf (Universiti Teknologi Mara, 2023)
COVID-19 has had an immense impact on many countries. This study assessed how the socio-demographic characteristics of hospitality employees working during the COVID-19 period in Malaysia influenced job insecurity, work engagement, financial concern, quality of life, and mental health. Data were collected from over 200 hospitality employees via an online questionnaire. Based on the results and the hypotheses tested, gender and age groups significantly influenced hospitality employees’ job insecurity and mental health. Additionally, changes in income level before and during COVID-19 significantly influenced hospitality employees’ job insecurity, work engagement, financial concern, quality of life and mental health. Our findings offer several implications for hospitality researchers and practitioners. To the best of our knowledge, this is the first known study that evaluated the socio-demographic influence on hospitality employees’ job insecurity, financial concerns, work engagements, quality of life, and mental health. Findings from this study contribute to the growing body of evidence on whether certain socio-demographic groups influence hospitality employees, particularly from an Asian country perspective like Malaysia. The researchers faced difficulties gathering data during the pandemic despite offering incentive opportunities. Therefore, future researchers should consider conducting a similar study in the post-pandemic period to gather data on the study variables for a comparison study.